Roach (Rutilus rutilus) populations respond to varying environment by altering size structure and growth rate - Olin, Mikko; Rask, Martti; Estlander, Satu; Horppila, Jukka; Nurminen, Leena; Tiainen, Joni; Vinni, Mika; Lehtonen, Hannu
2017